Effectiveness of leuprolide acetate administered monthly compared to three-monthly in the treatment of central precocious puberty: evaluation at the end of treatment - Thaneetrakool, Thanaporn; Aroonparkmongkol, Suphab; Numsriskulrat, Nattakarn; Supornsilchai, Vichit; Wacharasindhu, Suttipong; Srilanchakon, Khomsak (Frontiers in Endocrinology, 2024)
Introduction Gonadotropin-releasing hormone (GnRH) analogs are the standard treatment for central precocious puberty (CPP). Although there are numerous varieties of GnRH agonists, the effectiveness of 1-monthly compared with 3-monthly Leuprolide acetate is still restricted. The objective of this study was to evaluate the outcomes of CPP treatment with Leuprolide acetate at a 1-monthly dosage of 3.75 mg, in comparison to a dosage of 11.25 mg administered every 3 months. Method This retrospective cohort study involved 143 girls diagnosed with CPP with 72 of them receiving the monthly treatment regimen and 71 receiving the 3-monthly treatment regimen. Anthropometric measurements were compared at the start and end of the therapy. The rates and level of LH suppression were assessed six months after therapy. Results The regimen administered every 3 months showed more significant suppression of LH. The 3-monthly group showed lower actual height and degree of bone age advancement at the end of therapy. However, the predicted adult height (PAH) remained comparable in both groups. Conclusion The 3-monthly treatment showed greater hormonal and growth suppression effects, but there was no significant difference in PAH between the two groups.